Effects of Newcastle Disease Virus on Gene Expression Profiling, and Nitric Oxide and Glutathione Production in MCF-7 Breast Canser Cell Line - Ali, Mohamed Kalid (2011)
Breast cancer is a major cause of death for many women around the world. Progress has been made in the survival of breast cancer patients due to improved understanding of the molecular processes, diagnostic techniques and knowledge of the treatment using chemotherapy, radiotherapy, and virotherapy. The field of virotherapy has emerged from the past decade by using oncogenic viruses to selectively kill cancerous cells without harming normal cells. Newcastle disease virus (NDV), an avian paramyxovirus, induces apoptosis in a variety of human malignant cells such as breast cancer cells. In this study, the cytolytic properties of NDV strain AF2240 on gene expression profiling, measurement of Nitric oxide (NO) free radical and Glutathione antioxidant (GSH) were investigated by using RT-PCR, capillary electrophoresis, flow cytometry both under normoxic and hypoxic condition. Multiplex Gene Expression Kit was used whereby the relative expressions of 25 different genes were measured at the mRNA level. The results showed that treatment of MCF7 cells with NDV caused apoptosis, NO production and GSH depletion and changed the expression level of most of the genes involved in tumour progression, cell cycle regulation, cell growth and differentiation, apoptosis, cancer suppression, and DNA damage, as measured by RT-PCR and capillary electrophoresis. Since the mode of apoptosis by NDV is NO and GSH dependent, comparisons of NDV with NO-Donors such as DETA-NONOate and NO-Scavengers like cPTIO were also studied. Increased production of Nitric oxide (NO) and depleted levels of Glutathione (GSH) after treatment of NDV at normoxic condition compared NDV at hypoxic condition were observed. However, addition of DETA-NONOate to MCF-7 cells has induced NO production, GSH depletion. Moreover, NO production and apoptosis were attenuated, and GSH increased after addition of cPTIO either alone or with combination of either NDV or DETA-NONOate to the MCF-7 cells. In addition to the above, co-treatment of NDV+DETA-NONOate depleted NO production and cell death compared to the treatment of NDV alone to cells. From this study, it was concluded that NDV induces apoptosis, Gene expression, NO production and GSH depletion in MCF-7 cells which makes it an effective anticancer agent due to its ability to kill breast cancer cell lines in normoxic and hypoxic conditions.